2020
DOI: 10.25165/j.ijabe.20201302.4802
|View full text |Cite
|
Sign up to set email alerts
|

Gases emissions estimation and analysis by using carbon dioxide balance method in natural-ventilated dairy cow barns

Abstract: Contaminated gases emissions from livestock industry are becoming one of the most significant contributors to the increasingly serious environmental pollution. To find a way to reduce gases emissions, it is essential to reveal the factors that can affect the gases emissions. In this study, the concentrations of typical gases (including ammonia (NH 3), carbon dioxide (CO 2), hydrogen sulfide (H 2 S), and sulfur dioxide (SO 2)) generated from naturally-ventilated dairy cow barns were detected through the sample-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
2
8
0
1
Order By: Relevance
“…This is due to the fact that the main source of CO 2 and CH 4 can be attributed to enteric fermentation and respiration [35]. In detail, eructation from cows has been reported as the major source for CH 4 release in ruminants [36]. Moreover, for the same kind of housing system under study, it was found that the CO 2 released from manure was less than 5% of the total CO 2 production due to the absence of the deep-litter [37].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that the main source of CO 2 and CH 4 can be attributed to enteric fermentation and respiration [35]. In detail, eructation from cows has been reported as the major source for CH 4 release in ruminants [36]. Moreover, for the same kind of housing system under study, it was found that the CO 2 released from manure was less than 5% of the total CO 2 production due to the absence of the deep-litter [37].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation result between v t and v t+k is shown in Figure 2. The correlation between v t and v t+k is negatively correlated with k. When k is 15 s, the correlation coefficients under the three driving modes are 0.92, 0.90, and 0.91, which are all greater than 0.9, showing a strong correlation (p<0.01) [15] . When k is 20 s, the correlation coefficients in the three driving modes are 0.90, 0.87, and 0.90, respectively, which are slightly lower than when k is 15 s, but the correlation coefficients in both manual and unmanned driving modes are still greater than 0.9.…”
Section: Kinematic Sequence Division and Reliability Examination Of D...mentioning
confidence: 92%
“…The average wind speed, relative humidity, and temperature were 2.2 m/s, 32%, and 27.6 • C, respectively. Zou et al, (2020) reported that the emission rates from naturally ventilated dairy barns in North China were approximately 1.52 g/AU/h (1 to 8 ppm) for ammonia, 0.001 g/AU/h for hydrogen sulfide, and 0.002 g/AU/h for sulfur dioxide, respectively [35]. In another study from Canada, the emission rates from a dairy barn were approximately 26.5 to 97.5 mg/min (2.1 to 7.8 mg/AU/h) for PM 2.5 and 0.45 to 1.78 g/AU/h (1.9 to 3.1 ppm) for ammonia, respectively [36].…”
Section: Summary Of Measurement Datamentioning
confidence: 99%
“…Bjerg et al, (2012) reported that NH 3 emissions were higher in the morning (before noon) because animals urinated more at this time [37]. NH 3 emissions were lower at night because of reduced feeding and defecation [35]. Other studies also showed that ammonia concentrations during the daytime were lower than those during the nighttime.…”
Section: Diurnal Patterns Of Fine Particles and Gaseous Pollutant Con...mentioning
confidence: 99%